THE ROLE OF POOR GALAXY CLUSTERS FOR STUDYING SUPERCLUSTER STRUCTURE - Panko, E. A. (Одеські астрономічні публікації, 2008)
The distribution of galaxy clusters is analyzed in regions of 6 galaxy superclusters with both measured and estimated redshifts. The positions of ACO and APM galaxy clusters in the regions are compared with the positions of galaxy clusters and groups from a new catalogue based on the Muenster Red Sky Survey. The locations of galaxy clusters and groups are shown on 10° x 10° maps of the fields. A comparison is made between maps that include all galaxy clusters and groups, rich and poor clusters, and only rich clusters. The resulting large-scale structure in the regions is described in detail on the basis of both rich and poor clusters, and a new catalogue is produced that is convenient for further study of galaxy superclusters.